FEATURES OF THERMAL-HYDRAULIC CALCULATIONS OF PIPELINES FOR BIOGAS PRODUCTION SYSTEMS - Hryhorskyi, S. Ya.; Zapukhliak, V. B.; Pasichnyk, F. O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
Hydraulic and thermal processes of pipeline transport in biogas production systems have been investigated. An algorithm for thermal-hydraulic calculation for slurry pipelines and sewer pipelines has been developed, which takes into account variable physical and chemical properties, heat exchange with the ground (determination of heat transfer coefficients, similarity criteria) and hydraulic resistance (based on Bernoulli's equation and Darcy-Weisbach's dependence). This allows predicting the temperature of the transported medium along the length of the pipeline, as well as the total head and pressure losses in the system at a given capacity. For biogas pipelines, where the flow is considered isothermal, the algorithm provides for the calculation of the energy parameter and iterative selection of the optimal internal pipe diameter to ensure the specified nominal productivity and the minimum permissible final pressure. Based on the calculations for manure pipelines and sewer pipelines, a reasonable selection of pumping equipment was made according to the criteria of productivity and required head. It was established that the hydraulic characteristics of the manure pipeline significantly depend on the mass content of dry substances, the average pumping temperature and the energy carrier flow regime.